Sosialisasi Teknik Tata Rias Wajah Korektif Bagi Guru Tata Busana di Forum MGMP Busana Kabupaten Semarang - Sofia Daniati; Widiati Alifah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Teachers are figures who occupy a position and play an important role in education. Therefore, the teacher's performance in teaching is one of the important things in transferring knowledge. One performance that needs to be considered for a teacher is facial makeup. The best impression can be seen from the appearance of a teacher. Because the appearance will be seen first by all students. A good appearance can be interpreted by looking neat, clean, and attractive in terms of clothing, hair makeup and most importantly facial makeup. The purpose of the socialization of corrective makeup techniques is so that teachers can know corrective makeup techniques to provide skills, enthusiasm and motivation for teachers to be more creative in applying makeup in beautifying their appearance, especially when they teach. This teacher service activity teaches teachers how to apply their own makeup that is tailored to the occasion they are doing. This activity was carried out by delivering material using lecture and demonstration methods so that participants could see firsthand the technique of applying cosmetics to corrective makeup. After that, the participants held a discussion session with the resource person and continued the evaluation of the activity by asking several questions to the students. The enthusiasm of the trainees can be seen from the many questions asked about good cosmetics used for corrective makeup.